Bioremediation of Wastewater by Iron Oxide-Biochar Nanocomposites Loaded with Photosynthetic Bacteria - He, Shiying; Zhong, Linghao; Duan, Jingjing; Feng, Yanfang; Yang, Bei; Yang, Linzhang (Frontiers in Microbiology, 2017)
It has been reported that bacteria-mediated degradation of contaminants is a practical and innocuous wastewater treatment. In addition, iron oxide nanoparticles are wastewater remediation agents with great potentials due to their strong adsorption capacity, chemical inertness and superparamagnetism. Therefore, a combination of nanoparticles and microbes could produce a very desirable alternative to conventional wastewater treatment. For this purpose, we first prepared Fe3O4/biochar nano-composites, followed by loading photosynthetic bacteria (PSB) onto them. It was found that Fe3O4/biochar nano-composites exhibited a high adsorption capacity for PSB (5.45×109 cells /g). The efficiency of wastewater pollutants removal by this PSB/Fe3O4/biochar agent was then analyzed. Our results indicated that when loaded onto Fe3O4/biochar nano-composites, PSB’s nutrient removal capability was significantly enhanced (P<0.05). This agent removed 83.1% of chemical oxygen demand (COD), 87.5% of NH4+, and 92.1% of PO43- from the wastewater in our study. Our experiments also demonstrated that such composites are outstanding recyclable agents. Their nutrient removal capability remained effective even after five cycles. In conclusion, we found the PSB/Fe3O4/biochar composites as a very promising material for bioremediation in the wastewater treatment.